Prevalência e fatores associados à infecção pelo M. tuberculosis entre agentes comunitários de saúde - Rogerio, Wesley Pereira (2013)
Introduction: Tuberculosis is a millenary illness that nowadays constitutes serious problem of public health in the whole world. In Brazil the proposal of decentralization of the actions to control this illness has been occurring and enhancing Communitarian Agents of Health Programs and Family Health as a useful strategy that contributes to control the endemic tuberculosis disease in the country. Objective: To estimate the prevalence and factors associated with latent infection with MTB among Community Health Workers working in primary health Municipalities priority for TB control - Cuiabá / MT, Manaus / AM, Salvador / BA and Vitória / ES. Methods: Cross-sectional study in which data were collected through a questionnaire with open and closed questions about personal characteristics, information about tuberculosis, use of preventive measures, etc.. Tuberculin test was applied, with readings after 48-72h by trained nurses, considering how cutting bridge positive 5 and 10 mm of induration. A multivariate analysis was performed using logistic regression. Were included in the model the variables associated with the outcome with p <0.1. Remained in the model the independent variables that remained associated with the outcome after adjustment (p <0.05). This study was approved by the Ethics Committee on Human Research of the Center for Health Sciences, Federal University of Espírito Santo, no registration CEP-07/2010 and Municipal Health, through a Letter of Introduction. Results: 322 Community Health Agents (ACS) agreed to participate voluntarily in the study by signing the consent form. Of these, 10 did not attend for reading, which are considered losses beyond what an individual was excluded because of rapid HIV testing be positive, resulting in a final sample of 311 participants. Also in relation to ACS screened, positive tuberculin test, taking into account the test cutoff of 10 mm and 5 mm of induration, was 37.30% (95% CI: 0.31 to 0.42) and 57.88% (95% CI: 0.52-0.63), respectively. Conclusions: It is necessary to carry out a program of tuberculin test, routine, combined with interventions to reduce the risk of nosocomial transmission, as well as further studies to evaluate the effectiveness of new tests for latent tuberculosis.